Analisis Prioritas Strategi Penanggulangan Kemiskinan Kota Banjarmasin - Rakhmatullah R; Ahmad Yunani; Muhammad Anshar Nur; Muhammad Rusmin Nuryadin (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2025)
This study aims to comprehensively analyze and determine the priority strategies for poverty alleviation in Banjarmasin City, with a specific focus on cultural poverty, which remains the most dominant and deeply rooted form of poverty in the community. The research method combines Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis and the Analytical Hierarchy Process (AHP). The SWOT approach is employed to identify various internal and external factors influencing the effectiveness of poverty alleviation programs, as well as to formulate relevant and applicable strategic alternatives. Meanwhile, the AHP method is utilized to determine the priority order of these strategies based on expert assessments and stakeholder evaluations who possess expertise in social and economic development. The data were collected through in-depth interviews with seven key informants actively involved in the planning, implementation, and evaluation of poverty alleviation programs in Banjarmasin City. The findings indicate that the priority strategies that need to be developed include strengthening community empowerment institutions, improving human resource capacity, and enhancing the poverty data system to ensure validity, accuracy, and inter-agency integration. Policy recommendations emphasize the importance of cross-sectoral synergy, collaboration among development actors, and the implementation of evidence-based policies to ensure that poverty alleviation efforts are more effective, sustainable, and have a tangible impact on society.